Dragoš Kalajić – A Serbian critical attitude towards western culture and civilization - Kuzmanović, Nebojša (Napredak, 2025)
Abstract: Through the presentation of Dragoš Kalajić’s journalistic texts with the subject of war, as well as by emphasizing Kalajić’s participation in war conflicts during 1992-1995, the author strives to point to the basic corpus of values by which Kalajić was guided in life and which he fiercely defended, as well as to the higher, literary quality of his war reports. Analyzing Kalajić’s understanding of war and the place allotted to the writer in war, the author gives a clear picture of Kalajić’s “ideal” war correspondent, “the writer of God Mars”. He dedicates special attention to Kalajić’s observations regarding the character and spiritual strength of the fighters, who are the main bearers of the values about which he leaves a trace. In the conclusion, the author also gives a personal evaluation of Kalajić’s war records, as well as of the character of the war correspondent/writer standing behind them.